Transforming corporate governance through effective corporate social responsibility (CSR) and social entrepreneurship orientation in Nepal (Quest Journal of Management and Social Sciences, 2019)
Background: Different studies and development interventions have confirmed that socio-economic progress of a society is largely influenced by the exhibited level of corporate social responsibility (CSR) and social entrepreneurship orientation taken into account. This reality may serve in the same magnitude in context of present Nepalese corporate sector. However, different studies indicate that only a limited number of organizations are involved in such activities in the present context of Nepal. On the other hand, truthful participation with corporate social responsibility (CSR) related initiatives has been made mandatory in many countries thereby governing the CSR initiatives by defined rules and regulations.Objectives: The thrust of this paper was to understand the magnitude and direction of CSR and social entrepreneurial orientation of the Nepalese corporate sector, its current state, issues, challenges and ways forward.Methods: Accomplished on qualitative paradigm of study as a blend of guided literature reviews, seminar discourses and general situation observation and analyses, it may be claimed as a developmental discourse.Results: The Nepalese corporate sector has been positively inclined towards enhancement of brand image, reputation and societal relationship by means of truthful engagement in CSR and societal entrepreneurship initiatives.Conclusions: The attainment of socio-economic well-being can be witnessed by implementing effective CSR and social entrepreneurship initiatives. Insufficient preparedness of the public agencies with lack of follow-up, financing crises, traditional corporate policies and procedures have been the impeding issues affecting the design and execution of CSR and social entrepreneurship initiatives at present in Nepal.Implications: Required strict policy regulations at governing level and effective programming at implementation at corporate or industry level.